Taṭwīr Māddah al-Kitābah Fī Kitāb Bahasa Arab Madrasah Aliyah 2020 Bi Biṭṭāqah at-Takammulah Li Tarqiyah Qudrah aṭ-Ṭālibāt `Alā Tarkīb al-Jumal al-Mufīdah Bi Ma`had Darul Muta`allimīn Meulaboh: Darul Muta’allimin Meulaboh ببطاقة التكملة لترقية قدرة الطالبات على تركيب الجمل المفيدة بمعهد Bahasa Arab Madrasah Aliyah 2020 تطوير مادة الكتابة في كتاب - Hafnidar, Hafnidar; Falah, Moch. Fajarul (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
Writing is one of the four most important language skills for students because it reveals the results of what the learner has achieved from the language system. This thesis is entitled “Development of kitabah material in the 2020 Madrasah Aliyah Arabic Language Book with At-Takammulah bithaqah media to improve students' ability to compile the number of mufidah in Dayah Darul Muta'allimin”. The researcher found the problem that female students had difficulty in composing/composing perfect sentences. Students do not master vocabulary, they do not understand qawaid in constructing perfect sentences, both ismiyah and fi'liyah sentences. The purpose of this research is to find out how the development of kitabah material using bithaqah At-Takammulah media and to find out its effectiveness and to find out students' responses to the development of kitabah material using bithaqah at-takmilah media. This study used the R&D (Research and Development) method with the research instruments used were direct observation, questionnaires, and tests. Researchers took 29 class X students as a sample. As for data analysis techniques, researchers used the T-test formula from the SPSS program. And the results obtained from this study were 87.67%. The test results show that the use of At-Takammulah bithaqah media is effective in improving students' ability to compose perfect sentences. This is based on the results of Sig.0.05. This shows that Ha is accepted.